The Effect of Extraction Time Variation on Caffeine Content in Robusta Coffee Extract using Ultrasound-Assisted Extraction Method - Anggraini, Amelia Putri; Fildzah Arifah, Mitsalina; Sayyidah Yahya , Fina Ummu; Nurhasanah, Devika (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2025)
West Lampung Robusta coffee has a higher caffeine content than other types of coffee. The variations in extraction time in ultrasound-assisted extraction (UAE) produced different caffeine contents than conventional extraction methods. This study aims to determine extraction time variation (15, 30, 45) influences caffeine contents in roasted coffee beans. The organoleptic test and alkaloid test evaluated Robusta coffee qualitatively. The extract obtained was measured by measuring the % MC, yield value, and wavelength scanning. Quantitative analysis using UV-Vis Spectrophotometry determined the caffeine content with different extraction times, and then each group was assessed using SPSS software. The coffee bean powder was dark brown, had a distinctive coffee aroma, bitter taste, and smooth texture, and contained alkaloids with the Mayer, Wagner, and Dragendorff tests. The yield and % water content of extract at 30 (36.938%; 6.39%) were higher than at 15 (24.111%; 6.07%) and 45 minutes (22.170%; 6.37%). Alkaloids of the extract were investigated at a wavelength of 273 nm. Caffeine contents were 0.977 ± 0.018 mgCE/mg at the 15, 0.792 ± 0.054 mgCE/mg at the 30, and 0.979 ± 0.026 mgCE/mg at the 45 minutes in significant (P<0.05). In conclusion, the difference in extraction time impacted the caffeine content of the robusta coffee bean.